Research Progress on the use of Plant Allelopathy in Agriculture and the Physiological and Ecological Mechanisms of Allelopathy - Cheng, Fang; Cheng, Zhihui (Frontiers in Plant Science, 2015)
Allelopathy is a common biological phenomenon by which one organism produces biochemicals that influence the growth, survival, development, and reproduction of other organisms. These biochemicals are known as allelochemicals and have beneficial or detrimental effects on target organisms. Plant allelopathy is one of the modes of interaction between receptor and donor plants and may exert either positive effects (e.g., for agricultural management, such as weed control, crop protection, or crop re-establishment) or negative effects (e.g., autotoxicity, soil sickness, or biological invasion). To ensure sustainable agricultural development, it is important to exploit cultivation systems that take advantage of the stimulatory / inhibitory influence of allelopathic plants to regulate plant growth and development and to avoid allelopathic autotoxicity. Allelochemicals can potentially be used as growth regulators, herbicides, insecticides and antimicrobial crop protection products. Here, we reviewed the plant allelopathy management practices applied in agriculture and the underlying allelopathic mechanisms described in the literature. The major points addressed are as follows: (1) Description of management practices related to allelopathy and allelochemicals in agriculture. (2) Discussion of the progress regarding the mode of action of allelochemicals and the physiological mechanisms of allelopathy, consisting of the influence on cell micro- and ultra-structure, cell division and elongation, membrane permeability, oxidative and antioxidant systems, growth regulation systems, respiration, enzyme synthesis and metabolism, photosynthesis, mineral ion uptake, protein and nucleic acid synthesis. (3) Evaluation of the effect of ecological mechanisms exerted by allelopathy on microorganisms and the ecological environment. (4) Discussion of existing problems and proposal for future research directions in this field to provide a useful reference for future studies on plant allelopathy.